2020
DOI: 10.3390/ijms21051588
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A (RPA) Mediates Radio-Resistance of Glioblastoma Cancer Stem-Like Cells

Abstract: Glioblastoma (GBM) is among the deadliest of solid tumors with median survival rates of approximately 12–15 months despite maximal therapeutic intervention. A rare population of self-renewing cells referred to as GBM cancer stem-like cells (GSCs) are believed to be the source of inevitable recurrence in GBM. GSCs exhibit preferential activation of the DNA damage response pathway (DDR) and evade ionizing radiation (IR) therapy by superior execution of DNA repair compared to their differentiated counterparts, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…Consequently, HAMNO elevates DNA replication stress and mitigates tumor growth ( 350 ). A recent report demonstrates that HAMNO sensitizes glioblastoma cancer stem-like cells to ionizing radiation ( 351 ). The potential of other RPA inhibitors ( 352–356 ) as cancer therapeutics or as chemosensitizing agents needs to be validated.…”
Section: Targeting Rpa For Effective Cancer Therapymentioning
confidence: 99%
“…Consequently, HAMNO elevates DNA replication stress and mitigates tumor growth ( 350 ). A recent report demonstrates that HAMNO sensitizes glioblastoma cancer stem-like cells to ionizing radiation ( 351 ). The potential of other RPA inhibitors ( 352–356 ) as cancer therapeutics or as chemosensitizing agents needs to be validated.…”
Section: Targeting Rpa For Effective Cancer Therapymentioning
confidence: 99%
“…Replication protein A1 (RPA1) is a heterotrimeric ssDNA‐binding protein that participates in DNA replication and is required for each of the three major DNA repair pathways: NER, BER, and DSBs repair. It is found that RPA loss either by shRNA‐mediated silencing or chemical inhibition (HAMNO) impairs the survival and self‐renewing potential of GSCs (glioblastoma cancer stem‐like cells) while increasing their sensitivity to IR by impairing the DNA repair capacity of GSCs (Pedersen, Anne, Elbaek, Vitting‐Serup, & Hamerlik, 2020). Depletion of RPA1 increases CNE‐2R (human radioresistant nasopharyngeal carcinoma cell line) and TE‐1 R (radioresistant oesophageal cancer cells) cell radio‐sensitivity to X‐rays by impairing Rad51 recruitment to damage sites, contributing to G2/M phase arrest (Di, Sanyuan, Hong & Dahai, 2014; Z. Zhang et al, 2018).…”
Section: Strategies To Enhance Radio‐sensitivity To Rtmentioning
confidence: 99%
“…The success of therapy can be thwarted by features of cancer stem cells (CSCs) such as self-renewal and maintenance of tumor characteristics 47 . The presence of CSCs in glioma has been pointed out, which can help design and test new therapies for glioma 48,49 . Despite surgery and chemotherapy, 70% of patients are resistant to chemotherapy This resistance can be traced back to the CSCs, and the relevant research required this aspect to be kept in mind when designing new strategies 50 .…”
Section: Discussionmentioning
confidence: 99%